Poverty and Food Security: a reality in ASEAN countries - Imam Mukhlis; Ignatia Martha Hendrati; Özlem Sökmen Gürçam; Sugeng Hadi Utomo (Jurnal Ekonomi dan Studi Pembangunan, 2021)
This study aims to analyze the linkages of food security,food price index,economic growth,agriculture sector and population living below the poverty line in several ASEAN countries. ASEAN countries that became the objects of this study included Indonesia,Malaysia, Philippines, Thailand, Cambodia and Myanmar. The data used in the study were data from the period 2012-2017. These data included percentage of population living below the poverty line, food security index, food price index, contribution of agricultural sector to gross domestic product,economic growth rate and population. These data are available in the Asian Development Bank publication. Data analysis method used was panel data with least square method.  The results of this study concluded that food security rate, economic growth, and contribution of the agricultural sector to gross domestic product have a significant but negative impact on poverty rates. Meanwhile, the population had a positive and significant impact on poverty rates in various ASEAN countries.